Question #22a38
1 Answer
Explanation:
To simplify this expression, or any expression, a good start would be putting the binomial before the polynomial. This will make it a lot easier to multiply. In this case, it is already this way.
Now we can begin to multiply.
Take the
Then take the
(x - 3)(x^2 - 6x + 8) (x−3)(x2−6x+8)
(color(blue)(x) - 3)(color(green)(x^2) - 6x + 8) (x−3)(x2−6x+8) color(orange)(->) x * x^2 color(orange)(->) color(red)(x^3) →x⋅x2→x3
(color(blue)(x) - 3)(x^2 (x−3)(x2 color(green)( - 6x) + 8) −6x+8) color(orange)(->) x * -6x color(orange)(->) color(red)(-6x^2) →x⋅−6x→−6x2
(color(blue)(x) - 3)(x^2 - 6x (x−3)(x2−6x color(green)( + 8)) +8) color(orange)(->) x * 8 color(orange)(->) color(red)(8x) →x⋅8→8x
(x (x color(red)( - 3))(color(green)(x^2) - 6x + 8) −3)(x2−6x+8) color(orange)(->) -3 * x^2 color(orange)(->) color(red)(-3x^2) →−3⋅x2→−3x2
(x (x color(red)( - 3))(x^2 −3)(x2 color(green)( - 6x) + 8) −6x+8) color(orange)(->) -3 * -6x color(orange)(->) color(red)(18x) →−3⋅−6x→18x
(x (x color(red)( - 3))(x^2 - 6x −3)(x2−6x color(green)( + 8)) +8) color(orange)(->) -3 * 8 color(orange)(->) color(red)(-24) →−3⋅8→−24
Now all we have to do is add the terms that we got and simplify.
x^3 + (-6x^2) + 8x + (-3x^2) + 18x + (-24) x3+(−6x2)+8x+(−3x2)+18x+(−24)
x^3 - 6x^2 + 8x - 3x^2 + 18x - 24 x3−6x2+8x−3x2+18x−24
x^3 - 9x^2 + 26x - 24 x3−9x2+26x−24
As you can see, when we simplify our initial expression, we get our answer which is